2016
DOI: 10.1002/jclp.22338
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Revised Interpersonal Theory of Depression Using a Laboratory Measure of Excessive Reassurance Seeking

Abstract: ERS is a potent predictor of stress and subsequent depression. Our findings underscore the need to better understand factors (e.g., cognitions, partner characteristics) that may determine whether ERS behaviors beget interpersonal stress and rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 38 publications
1
30
0
2
Order By: Relevance
“…This result is in line with the interpersonal relationship theory of depression [63]. Good interpersonal relationships enable college students to obtain more spiritual support and help, thus reducing the occurrence of anxiety and depression [64]. This study showed that eating habits and sleeping time were associated with anxiety symptom, depressive symptom, and the comorbidity of anxiety and depressive symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…This result is in line with the interpersonal relationship theory of depression [63]. Good interpersonal relationships enable college students to obtain more spiritual support and help, thus reducing the occurrence of anxiety and depression [64]. This study showed that eating habits and sleeping time were associated with anxiety symptom, depressive symptom, and the comorbidity of anxiety and depressive symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…Although depression is generally more strongly associated with suicide ideation than attempts (Nock et al 2013), it is possible that Interpersonal Loss events triggered depressive episodes in our sample, or worsened symptoms, which in turn were more proximally related to suicide attempts. Another possibility is that adolescents with more severe depressive symptoms generated more Interpersonal Loss events (e.g., partner-initiated break-ups or arguments; see Stewart and Harkness 2015, 2017) and these in turn contributed to suicide attempts. Future research employing more precise measures of clinical characteristics in time frames that definitively precede assessments of stress and STBs is needed to elucidate potential dynamic relations between depression, interpersonal stressors, and suicide attempts in youth.…”
Section: Discussionmentioning
confidence: 99%
“…For example, excessive seeking of reassurance (Starr & Davila, 2008), negative evaluation from friends (Joiner & Timmons, 2002), and excessive self-disclosure regardless of social context (Rottenberg & Gotlib, 2004) have all been linked to depression. Such behaviors often solicit negative reactions from social partners, including domineering behavior, dismissiveness, or rejection (Horowitz, 2004; Locke et al 2017; McCullough, 2000; Stewart & Harkness, 2017; Starr & Davila, 2008), that, when an individual has strong emotional reactivity to close relationships, can cycle back to produce more negative emotions (Nezlek, Imbrie & Shean, 1994). Indeed, experience sampling studies show that social interactions characterized by less warm and more submissive behaviors are accompanied by more negative emotions (Sadikaj, Moskowitz, & Zuroff, 2011; Wang et al, 2014).…”
Section: Emotion Regulation Depression and Feedback Loopsmentioning
confidence: 99%